PEMODELAN STRUKTUR BAWAH PERMUKAAN LAPANGAN PANASBUMI BANDA BARU BERDASARKAN ANALISA DATA GRAVITASI - , AHMAD PADANG ARIFIN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The study using gravity method was done in Banda Baru geothermal field to identify reservoir and fault structure. This study area is about 15 km x 20 km with 171 data points that spread randomly. Data processing begins from the complete Bouguer anomaly mapping, which is transformed into a flat surface using the method Dampney, with a height of flat surface 600 meters and a depth of field equivalent of 9000 meters. Regional-residual anomaly separation has done using the upward continuation method at an altitude 900 meters. From the modeling results indicate constituent rocks of the study area is intrusive rock with a density of 2.8 gr/cm3, metamorphic rocks with density 2.6 gr/cm3 that included in the Tehuru complex, sandstones with a density of 2.5 gr/cm3 that included in the Fufa complex is assumed as a reservoir, coral limestone with a density of 2.3 gr/cm3 carrying alluvium with density of 2.2 gr/cm3. In the model also visible graben that formed by several faults structure.